La scène traumatique de Sarah Kane - Élisabeth Angel-Perez (Sillages Critiques)
Kane’s dramatic work reads like the paragon of the late 20th century traumatic stage. As early as in her first plays in which she opts for frontality and In-Yer-Face aesthetics, Kane constructs the stage as performative and even ontological : the very place of authentification of trauma. Kane also proposes a vision of trauma as repeating itself at different scales and her characters collapse the private self and the political subject in an all-encompassing Me-World. Finally, her latest plays essentialize her ash-poetry by exploring a theatre of paradox : trauma pierces holes in the fabric of life and obliteration is all there is to see onstage.